Distribution characteristics and environmental fate of PCBs in marine sediments at different latitudinal regions: Insights from congener profiles. (December 2020) - Deng, Zhaochao; Li, Xinkai; Chen, Chunlei; Zhang, Ning; Zhou, Hanghai; Wang, Heng; Han, Xibin; Zhang, Chunfang
Abstract: Sediments were sampled from Hangzhou Bay (HB), the South China Sea (SCS), and Antarctica (AZ) to better understand the distribution characteristics and environmental fate of polychlorinated biphenyls (PCBs) at different latitudes. Numerous PCB congeners (68) were detected among the sampling sites, supporting the ubiquity of PCB congeners. High and low chlorinated congeners dominated the PCB profiles of AZ and SCS, respectively, whereas the PCB homologues were evenly distributed in the HB. As a fraction of low chlorinated PCBs originates from an exogenous input, the low mean ratios of ∑Tetra-CBs to ∑PCBs and ∑Tetra-CBs to the sum of ∑Tri- and ∑Di-CBs suggest that microbial transformation of PCBs is weak in marine surface sediments, if any occurs at all. Furthermore, PCB contamination levels in marine sediments may be primarily influenced by latitude rather than pollution sources. Thus, the findings of this study suggest that Antarctica is becoming a prospective hotspot for PCBs. Highlights: Analyses of 200 PCBs were performed in marine sediments with different latitudes. No less than 68 PCB congeners were detected among all sampling sites. PCB-contamination level in marine sediment may be mainly influenced by latitudes. The Antarctica is becoming a prospective hotspot for PCBs. If any, the microbial transformation of PCBs was weak in the surface sediment.